Coordinated and Cooperative Control of Heterogeneous Mobile Manipulators. - Molina Fernández, María Fernanda (2018)
This paper proposes a multilayer scheme for the cooperative control of 2 n „d heterogeneous mobile manipulators that allows to transport an object in common in a coordinated way; for which the kinematic modeling of each mobile manipulator robot is performed. Stability and robustness are demonstrated using the Lyapunov theory in order to obtain asymptotically stable control. Finally, the results are presented to evaluate the performance of the proposed control, which confirms the scope of the controller to solve different movement problems.